PENGARUH FAKTOR KECERDASAN SPIRITUAL TERHADAP PRESTASI KERJA DOSEN SEKOLAH TINGGI MARITIM YOGYAKARTA (STIMARYO) - suyanti suyanti; Handoyo Widyanto; Supartini Supartini (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2020)
This research examines the implications of spiritual intelligence to the work performance of Yogyakarta Maritime College (STIMARYO) lecturers. The reseach problem is the influence of spiritual intelligence factor on Yogyakarta Maritime College lecturers' to their work achievement.This research is a quantitative study that uses primary data as the data source. The data were obtained from distributing questionnaires to Yogyakarta Maritime College lecturers. The data were analyzed using simple linear regression. The results of the research concluded that there was a positive and significant influence of the spiritual intelligence factors to the work achievement of Yogyakarta Maritime College lecturers. The existence of a positive influence is known from the regression coefficient of 0.534. The existence of a significant influence is known from the results of the F test and t test which get a significance value of 0.001 (< 0.05) which means that the independent variable has a significant effect on the dependent variable.Keywords: Influence, Spiritual Intelligence Factor, work achievementPenelitian ini meneliti implikasi kecerdasan spiritual terhadap prestasi kerja dosen Sekolah Tinggi Maritim Yogyakarta (STIMARYO). Masalah yang diteliti adalah pengaruh kecerdasan spiritual terhadap prestasi kerja dosen Sekolah Tinggi Maritim Yogyakarta. Penelitian ini merupakan penelitian kuantitatif yang menggunakan data primer sebagai sumber datanya. Data diperoleh dari penyebaran kuesioner kepada karyawan Sekolah Tinggi Maritim Yogyakarta. Data dianalisis menggunakan regresi linier sederhana. Hasil penelitian mendapatkan kesimpulan ada pengaruh positif dan signifikan dari faktor kecerdasan spiritual terhadap prestasi kerja dosen Sekolah Tinggi Maritim Yogyakarta. Adanya pengaruh positif, diketahui dari nilai koefisien regresi sebesar positif 0,534. Adanya pengaruh signifikan diketahui dari hasil uji F dan uji t yang mendapatkan nilai signifikansi 0,001 (< 0,05) yang berarti bahwa variabel bebas mempunyai pengaruh yang signifikan terhadap variabel terikat.Kata kunci: Pengaruh, Faktor Kecerdasan Spiritual, Prestasi Kerja